Perfil clínico-epidemiológico de pacientes com síndrome respiratória aguda grave pelo vírus Influenza A (H1N1) pandêmico no estado do Pará. - PINHEIRO, Lúcio José Moreira (2022)
At the beginning of 2009 the world faced a new epidemic caused by a new subtype of influenza virus A (H1N1). Mexico was the first country to report a new case concerning the flu and in a short time, similar cases have been reported in other countries, leaving on alert health authorities for a pandemic. The study referred to here is a clinical-epidemiological evaluation of patients with severe acute respiratory syndrome (SARS) caused by influenza virus A (H1N1) pandemic in the entire state of Para, watching the situation of patients, the presence of comorbidities, the offered treatment and clinical outcome is to improve the frame or possible death. This work was a cross-sectional study, retrospective, descriptive and analytical, whose sample was obtained through the research data via Information System for Notifiable Diseases (SINAN) based on the notification protocol form the Ministry of Health Cases of SARS in Para state associated with Influenza A (H1N1) pandemic occurred during the months of August 2009 to April 2010, with the occurrence of two epidemic waves (February and August to October/2009 to April/2010). Young patients with a mean age of 19 years, mainly female (64.2%%), women in the third trimester or who had a chronic lung disease or associated metabolic disease made up the majority of the sample, 28.1% of patients were from the upstate , 33.3% evolved to death. This work shows the severity of the flu virus (H1N1) pandemic in the state of Pará especially in patients belonging to risk groups.